KETERAMPILAN DASAR BERMAIN FUTSAL DAN KONDISI FISIK SISWA EKSTRAKURIKULER FUTSAL SMA NEGERI 6 PONTIANAK - Riski Kurniawan; Ahmad Atiq; Fitriana Puspa Hidasari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThe problem in this study is how the basic skills of playing futsal and the physicalcondition of extracurricular students at SMA Negeri 6 Pontianak are. the researchmethod used is the test and measurement method with tests of basic futsal skills andfutsal physical conditions consisting of 20 extracurricular participants. ”: 7 players orequal to (35%), “medium” category: 6 players or equal to (30%), “less” category: 5players or equal to (25%), and “very less” category: 1 player or equal to (5%). Fromthe overall data, the basic skills of playing futsal at SMA Negeri 6 Pontianak are inthe "Good" category. The physical condition test of the futsal extracurricularparticipants at SMA Negeri 6 Pontianak showed that the players in the "very good"category: 2 players or 10 percent in the "good" category: 5 players or 25 percent inthe "medium" category: 5 players or equal to (25%), “less” category: 7 players orequal to (35%), and “very less” category: 1 player or equal to (5%). With theseresults, the skill level of playing futsal of futsal extracurricular participants at SMANegeri 6 Pontianak is declared to be in the "Less" category.Keywords: Basic Futsal Technical Skills and Futsal Physical Condition